Teosofi, nasionalisme & elite modern Indonesia / Iskandar P.Nugraha; Editor, J.J Rizal dan Uswatul Chabibah - ISKANDAR P. Nugraha; RIZAL, J.J.; USWATUL Chabibah (Komunitas Bambu, 2011)
xxx, 210 hlm. : ilus. ; 21 cm.